Efisiensi Faktor Produksi dan Pendapatan Padi Sawah di Desa Masani Kecamatan Poso Pesisir Kabupaten Poso - Effendy Effendy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
This research aimed to identify the use efficiency of production factors and the income level of wetland rice farm at Masani Village of Poso Pesisir Sub district of Poso Regency. This Location was purposively determined. Respondents were determined using a simple random sampling method. The number of samples was 63 people taken from population of 167 people. The CobbDouglas production function was used to analyze the use efficiency of wetland rice farm production factors and the level of income was descriptively analyzed. Results of the research showed that (1) factors such as farm area size, seed, fertilizer and labor were not efficiently used in the wetland rice farm at Masani Village of Poso Pesisir Sub district, so increasing these factors are required to reach maximal production and income, and (2) the income of the wetland rice farmers at Masani Village of Poso Pesisir Sub district can be divided into three levels included low income equal to 30.16%, medium 38.10%, and high 31.74%.